2017
DOI: 10.5140/jass.2017.34.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Tomography Reconstruction of Ionospheric Electron Density with Empirical Orthonormal Functions Using Korea GNSS Network

Abstract: In South Korea, there are about 80 Global Positioning System (GPS) monitoring stations providing total electron content (TEC) every 10 min, which can be accessed through Korea Astronomy and Space Science Institute (KASI) for scientific use. We applied the computerized ionospheric tomography (CIT) algorithm to the TEC dataset from this GPS network for monitoring the regional ionosphere over South Korea. The algorithm utilizes multiplicative algebraic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…To improve on estimations of climatologic models and still obtain a full 3-D picture of the ionosphere, tomography techniques have extensively been applied (e.g., Hong et al, 2017;Raymund et al, 1990;Saito et al, 2016;Seemala et al, 2014;Ssessanga et al, 2015Ssessanga et al, , 2017Tsai et al, 2002). However, ionosphere tomography techniques have a deficiency of not being able to adequately spread observation information within the grid, specifically over remote areas where measurements are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…To improve on estimations of climatologic models and still obtain a full 3-D picture of the ionosphere, tomography techniques have extensively been applied (e.g., Hong et al, 2017;Raymund et al, 1990;Saito et al, 2016;Seemala et al, 2014;Ssessanga et al, 2015Ssessanga et al, , 2017Tsai et al, 2002). However, ionosphere tomography techniques have a deficiency of not being able to adequately spread observation information within the grid, specifically over remote areas where measurements are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a segment, the voxels that intersect a ray should first be identified. Although detailed procedures are not presented, finding such voxels using the AP approach (Hong et al 2017) can be implemented by an intersection test on the voxels inside the minimal bounding box (MBB) of the auxiliary plane. Nevertheless, the number of voxels to be tested remains large if the MBB is large.…”
Section: Overview Of the Sivt Approachmentioning
confidence: 99%
“…Wen et al (2007) and Zheng et al (2018) showed that iteration procedures in which the relaxation parameter is chosen dynamically improve convergence. Hong et al (2017) argued that tomographic inversion could be accelerated if many electron density unknowns are replaced by a few empirical orthonormal functions (EOFs). Regardless, a more generic way to accelerate inversion is to use parallel computing technology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations